Privatisasi Dalam Penyediaan Tenaga Listrik Untuk Kepentingan Umum - Dian Handayani; Elisatris Gultom (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
With the establishment of electricity as a branch of production that controls the lives of many people by the 1945 Constitution and Law Number 30 of 2009 concerning Electricity, the provision of sufficient and reliable electricity is the government's obligation. In the implementation of Law Number 30 of 2009 where the government stipulates that the provision of electricity for the public interest can also be carried out by private business entities, the focus of this research is (1) to find out whether the provision of electricity for the public interest is provided by private business entities. is a form of privatization of electricity as a branch of production that controls the lives of many people, and (2) to find out what the Government's authority is in setting electricity tariffs, especially electricity tariffs provided by private business entities. The method used in this journal is the normative juridical method, which takes the form of research on applicable laws and regulations, legal principles, court decisions, expert opinions and writings related to this journal. From the research results, it was found that the provision of electric power for public purposes is not only carried out by the government through PT PLN (Persero) but is also carried out by private business entities, namely by providing the same role. By giving this role, it can be concluded that there has been privatization in the supply of electricity for the public interest. The provision of electricity by private business entities is intended to assist the Government in providing sufficient and reliable electricity, especially for the business and industrial sectors, so that it can attract foreign investors to do business in Indonesia and the community's economy can develop. However, the government has the authority to set electricity tariffs for consumers or customers in each business area managed by private business entities and can be set differently, but this has consequences for household customers who in fact usually pay more than the tariff for home customers. stairs located within the PT PLN (Persero) business area. As a consequence, it is recommended that the government set tariffs for household and social customers in business areas managed by private business entities the same as rates for household and social customers in PT PLN (Persero) business areas. Electricity used by households and social groups still functions as a public good that controls the livelihoods of many people, which is different from electricity for business and industrial needs.